Advancement in Quebec Research on the Prevention of Risks Related to Occupational Exposure to Nanomaterials - Dolez, Patricia; Cloutier, Yves; Noël, Alexandra; Tabet, Lyes; Gautrin, Denyse; Debia, Maximilien; L’Espérance, Gilles; Hallé, Stéphane; Bahloul, Ali; Vinches, Ludwig (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2013)
SummaryThis article includes a presentation of the research priorities and achievements of the members of this nanotoxicology researcher group in the five following themes: toxicology, epidemiology, metrology/characterization, aerodynamic behaviour/ventilation, and protective equipment. The toxicology section includes a presentation of results relating to the respiratory effects of titanium dioxide (TiO2) nanoparticles in vivo and carbon nanotubes (CNT) in vitro and in vivo. Regarding occupational exposure to nanoparticles, studies that have been carried out include evaluations of mass and number concentrations, measurements of particle size distributions, as well as electron microscopy characterization of nanometric-sized particles. In the field of protective equipment, studies are being carried out to measure the penetration of nanoparticles through protective gloves and clothing under conditions simulating their use in workplaces. Furthermore, expertise has been developed at the IRSST on the measurement of filter efficiency in ventilation systems and respiratory protective equipment. Respiratory filter efficiency performance was evaluated under constant and variable airflows. The article ends with a description of the direct impacts on nanomaterial risk prevention related to the nanotoxicology researcher group.